Determinants of Halal Food Provision Among Restaurants in Iligan City Basis for Strategy Formulation - Jannah Qesma Gumama (Journal of Business and Halal Industry, 2026)
The growing demand for halal food has increased the need for local restaurants to provide food that complies with halal requirements. This study examines the determinants that influence the provision of halal food among local restaurants in Iligan City, Philippines. Using a descriptive, cross-sectional research design with a quantitative methodology, restaurants in Iligan City were surveyed with questionnaires to determine their level of awareness, the determinants influencing their provision of halal food options, the challenges that they encounter, and the extent of halal food provision. Results of the study indicated that most restaurants have good-to-high levels of awareness, with awareness of the importance of halal food having the highest mean, while awareness of the halal certification process had the lowest mean. Regression analysis indicated that social, marketing, and cultural determinants significantly influence the provision of halal food, while awareness and business values had no significant influence. Halal food options were found to be available at most local restaurants, though these options did not consistently meet strict halal standards. The main challenges identified include supply and ingredient issues, limited information and knowledge about halal food, and staff training. Based on these findings, it can be concluded that the provision of halal food by local restaurants in Iligan City is primarily influenced by social, marketing, and cultural factors, highlighting the need for certification assistance, staff training, and stronger government support to strengthen halal compliance in the restaurant industry.